Corn variety identification based on improved EfficientNet lightweight neural network - Xu, Jinpu; Lan, Jinhao; Lv, Guangjie; Ma, Dexin (Frontiers in Plant Science, 2025)
The authenticity of corn seeds is critical to yields and their market value. The screening of corn ears is an important step in the processing of corn seeds. In order to protect the intellectual property rights of corn varieties and realize intelligent ear screening, this article proposes an improved EfficientNet lightweight model, which uses deep learning technology to classify and identify corn ear images. First, 6529 RGB images of corn ears of five varieties were collected to construct a data set. Secondly, the number of MBConv modules in the EfficientNetB0 model was reduced, and the CBAM attention mechanism and dilation convolution were introduced to enhance the feature extraction capability. Finally, the Swish activation function was used to improve the stability of gradient transfer, and the SCD_EFTNet model was proposed. Experiments show that the proposed model has obvious advantages compared with mainstream models in indicators such as Recall, Precision, mAP, and inference time, and its mAP reaches 98.11%. The phenotypic characteristics of corn ears can be used to better classify and identify different varieties of corn, providing a reference for intelligent sorting of corn ears.